Novel Approaches To Fight Streptococcus pneumoniae - Maestro, Beatriz; Sanz, Jesus M. (Recent Patents on Anti-Infective Drug Discovery, 2007)
Streptococcus pneumoniae affects millions of people worldwide. It is responsible for a wide spectrum of serious illnesses such as pneumonia, meningitis and bacteraemia. The highest rate of pneumococcal disease (and the highest mortality) occurs in young children, as well as in the elderly and the immunocompromised patients. Identification of S. pneumoniae in diagnostic procedures may significantly improve thanks to the descripion of new PCR-derived techniques. Vaccination based on the polysaccharidic capsule, together with benzylpenicillin-derived drugs, constitute the current choices to tackle pneumococcal diseases. However, the wide serotype diversity of S. pneumoniae and the emergence of antibiotic-resistant strains is fostering the development of new methods to fight this microorganism. In this sense, patents documenting the use of novel antibiotics of the fluoroquinolone or tetracycline families have recently been described. Moreover, surface-associated proteins are receiving an increasingly special attention, as they are synthesized by most pneumococcal strains and play an important role in virulence. New patented protein-based vaccines take into consideration these polypeptides. In this article we present the main relevant characteristics of this pathogen and review the most recent methods that have been patented for the prevention, diagnostic and treatment of the pneumococcal diseases.
Keywords: antibiotic resistance